Explaining the persistence of factionalism in parties - Ó Muineacháin, Séin (Trinity College (Dublin, Ireland). Department of Political Science, 2012)
This thesis examines the causes of the persistence of factions in parties. It undertakes this analysis using both qualitative and quantitative methods by performing statistical analysis at the level of the country and the party. It also looks in depth at case studies in Japan, Botswana and Ireland.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin.